Evidence for early sedentism at Körtik Tepe, southeastern Turkey, during the Younger Dryas - Benz, Marion; Rössner, Corinna; Deckers, Kathleen; Riehl, Simone; Alt, Kurt W.; Özkaya, Vecihi (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
Location: Körtik Tepe, Province Diyarbakır, Southeastern Turkey, at the confluence of the River Tigris and the Batman Creek. Period: Younger Dryas to Early Holocene (10400-9200 BCE) Focus: Archaeological evidence for permanent occupation of the site; conditions favouring early sedentism at the intersection of two ecological regimes: the riverine environments and the steppe/tree-steppe mountain ranges of the hinterland; ecological and socio-economic impact of sedentism and of climatic changes from the Younger Dryas to the Early Holocene; interpretation of burial customs comparing evidence of daily practices and emerging differentiation in burial rituals. Methods: Archaeobotany, stable isotope analyses, modelling of radiocarbon sequences; holistic approach